What Happens During Recessions, Crunches and Busts? - Terrones, Marco (IMF Working Papers; Working Paper ;, 2008)
We provide a comprehensive empirical characterization of the linkages between key macroeconomic and financial variables around business and financial cycles for 21 OECD countries over the period 1960-2007. In particular, we analyze the implications of 122 recessions, 112 (28) credit contraction (crunch) episodes, 114 (28) episodes of house price declines (busts), 234 (58) episodes of equity price declines (busts) and their various overlaps in these countries over the sample period. Our results indicate that interactions between macroeconomic and financial variables can play major roles in determining the severity and duration of recessions. Specifically, we find evidence that recessions associated with credit crunches and house price busts tend to be deeper and longer than other recessions. JEL Classification Numbers: E32; E44; E51; F42.